FAKTOR APA SAJA YANG BERPENGARUH TERHADAP KINERJA UMKM? Study Kasus UMKM di Desa Batan Kabupaten Boyolali - Tiaradewi, Rischa; Ismunawan, Ismunawan (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
This study aims to determine whether there is an influence between Accounting Information Systems, Ability to Prepare Financial Reports, Basic Knowledge of Business and Use of Technology on MSME Performance. This type of research is a descriptive quantitative approach, with a quota sampling technique for sampling. The sample size used was 125 SMEs. The results of the study will show that the Accounting Information System has an effect on MSME Performance, the Ability to Prepare Financial Statements has an effect on MSME Performance, Business Basic Knowledge has no effect on MSME Performance and Technology Use has an effect on MSME Performance.